Violence against women and girls in Dorset, United Kingdom: an epidemiological study of perpetrators and locations based on police records - Jessica Pearcey; Barak Ariel; Vincent Harinam; Noy Assaraf (Humanities & Social Sciences Communications)
Abstract Violence against women and girls (VAWG) continues to be a prevalent phenomenon, yet where it is more likely to occur in the public domain and how offenders assault victims remain understudied areas of interest. This analysis is based on police records on VAWG from Dorset, United Kingdom (UK), using descriptive and spatial statistical methods alongside k-means longitudinal clustering. The spatial analysis uses hexagonal tessellations with a maximum area of 100 m² to identify VAWG hotspots. Findings reveal a significant concentration of public-place VAWG harm in a few spots: half of the reported VAWG occurred within just 2.6% of these hexagons. The study also illustrates a consistent trend in VAWG occurrences, with areas categorised as low, moderate, and high in VAWG counts and measured harm remaining constant over time. However, offenders responsible for the majority of counts and harm are not predominantly active in the hotspots with the highest counts and harm, which suggests a stochastic modus operandi rather than a fixation on specific locations. The identified VAWG hotspots and patterns in offender behaviour provide valuable insights for implementing targeted crime management strategies, and underscore the need to integrate factors like frequency, recentness, degree of harm, and geographical location to assess and address VAWG risks effectively.